ANALYSIS OF EMPLOYEE PERFORMANCE IN IMPROVING ADMINISTRATIVE SERVICES AT MOODULIO VILLAGE OFFICE, BONE DISTRICT, BONE BOLANGO - Tangahu, Selvira; Rachman, Azis; Wahdah, Ghoriqnah Fibahril (LP2M Universitas Bina Mandiri Gorontalo, 2025)
The objectives of this research are: 1) What is the level of employee performance in administrative services at Moodulio Village Office, Bone District, Bone Bolango Regency? 2) What improvements can be made to enhance employee performance and administrative services at Moodulio Village Office, Bone District, Bone Bolango Regency? This study uses a qualitative method with a case study approach, employing data collection techniques such as observation, interviews, and documentation. The research findings indicate that: 1) The level of employee performance in administrative services at Moodulio Village Office is affected by issues such as timeliness and frequent obstacles. These obstacles include network and electricity issues due to dependency on the Bolsel-Sulut region. When there is a power outage in the Bolsel-Sulut area, Moodulio Village also experiences power outages. Currently, most administrative tasks at Moodulio Village Office are managed online, making electricity and network connectivity crucial for online processing and document printing. 2) To improve employee performance and administrative services at Moodulio Village Office, one crucial step is to enhance the internet network infrastructure in the village office area. . This can be achieved through collaboration with internet service providers to ensure more stable, faster, and reliable connections. Such collaboration might involve developing physical infrastructure, such as installing fiber optic cables or upgrading existing network capacities, to meet the increasingly complex operational needs of the village office.